High intraindividual variability of CD30 expression in mycosis fungoides: implications for diagnostic evaluation and therapy. (October 2021) - Mitteldorf, Christina; Kampa, Franziska; Ströbel, Philipp; Schön, Michael P.; Kempf, Werner
Abstract : The correct interpretation of biomarkers, such as CD30, is critical and influences therapeutic decision. This retrospective multicenter study investigated 135 biopsy specimens of 95 patients with mycosis fungoides digitally for CD30 expression and CD30 staining pattern, histomorphologic criteria and presence of eosinophils in relation to tumor stage. We focused on the variability in different tissue samples from the same patient at the same and at different time points. We found that 90% of the samples showed CD30 expression (cut-off: ≥1%). The staining was predominantly cytoplasmic, a Golgi pattern was the exception. In patients with multiple biopsies, a high variability was found, especially in biopsies taken at different time points. CD30 expression and eosinophils were more commonly found in advanced stages. In mycosis fungoides, the investigation of multiple tissue samples for CD30 expression improves the assessment of this therapeutic target. Analysis of only a single skin biopsy specimen might lead to misinterpretation of CD30 and bears the risk of inadequate and potentially unfavorable therapeutic decisions.